Preservative-free tafluprost in the treatment of naive patients with glaucoma and ocular hypertension - Lanzl, Ines (Dove Medical Press, 2013)
PURPOSE: The study reported here investigated the efficacy, tolerability, and safety of the preservative-free prostaglandin analog tafluprost 0.0015% in treatment-naive patients. PATIENTS AND METHODS: Data were collected in two non-interventional, prospective, multicenter, observational, open-label studies of identical design that were conducted in Germany and the Czech Republic. All subjects received preservative-free tafluprost 0.0015% once daily. Intraocular pressure (IOP) levels were recorded for each eye at untreated baseline and 3 months after initiation of medical treatment. The primary outcome was change in mean IOP from baseline to month 3. In the primary open-angle glaucoma (POAG) and ocular hypertension (OH) patient subgroups, analyses were stratified by the level of baseline IOP: ≥20 to 23 mmHg versus ≥24 mmHg. In addition, responder rates and the achievement of pre-specified IOP levels at month 3 were evaluated. Local tolerance of preservative-free tafluprost was evaluated by the patients at final visit. Overall satisfaction with the medical treatment was evaluated by both patients and physicians. All adverse events were recorded. RESULTS: A total of 579 treatment-naive patients with POAG (n = 349), OH (n = 105), normal tension glaucoma (n = 71), exfoliative glaucoma (n = 27), or other glaucomas (n = 27) were included in this observational study. Mean IOP level at baseline for all patients was 23.6 ± 4.0 mmHg. Mean IOP at month 3 was 16.8 ± 2.9 mmHg (−28.8% vs baseline). At month 3, significant reductions in mean IOP (P < 0.001) were seen in all patients and all subgroups. Preservative-free tafluprost lowered mean IOP significantly in patients with POAG and OH with IOP levels ≥ 20 to 23 mmHg from 21.9 ± 1.1 mmHg at baseline to 16.5 ± 2.2 mmHg, and in the subgroup with IOP levels ≥ 24 mmHg from 26.2 ± 2.4 mmHg to 17.9 ± 2.4 mmHg. In the subgroups of patients with POAG and OH, an IOP response ≥20%, ≥30%, and ≥40% was achieved by 83.4%, 44.1%, and 12.8%, respectively. Overall, patients with higher baseline IOP values showed a better response than patients with lower baseline IOP levels. Preservative-free tafluprost was well tolerated and safe. After 3 months, 97.9% of all patients remained on therapy. CONCLUSION: In this real-world observational study, treatment with once-daily preservative-free tafluprost proved efficacious, well tolerated, and safe in treatment-naive patients.